Increased 5-hydroxymethylcytosine and decreased 5-methylcytosine are indicators of global epigenetic dysregulation in diffuse intrinsic pontine glioma - Ahsan, Sama (Acta Neuropathol Commun, 2014)
INTRODUCTION: Diffuse intrinsic pontine glioma (DIPG) is a malignant pediatric brain tumor associated with dismal outcome. Recent high-throughput molecular studies have shown a high frequency of mutations in histone-encoding genes (H3F3A and HIST1B) and distinctive epigenetic alterations in these tumors. Epigenetic alterations described in DIPG include global DNA hypomethylation. In addition to the generally repressive methylcytosine DNA alteration, 5-hydroxymethylation of cytosine (5hmC) is recognized as an epigenetic mark associated with active chromatin. We hypothesized that in addition to alterations in DNA methylation, that there would be changes in 5hmC. To test this hypothesis, we performed immunohistochemical studies to compare epigenetic alterations in DIPG to extrapontine adult and pediatric glioblastoma (GBM) and normal brain. A total of 124 tumors were scored for histone 3 lysine 27 trimethylation (H3K27me3) and histone 3 lysine 9 trimethylation (H3K9me3) and 104 for 5hmC and 5-methylcytosine (5mC). An H-score was derived by multiplying intensity (0–2) by percentage of positive tumor nuclei (0-100%). RESULTS: We identified decreased H3K27me3 in the DIPG cohort compared to pediatric GBM (p < 0.01), adult GBM (p < 0.0001) and normal brain (p < 0.0001). H3K9me3 was not significantly different between tumor types. Global DNA methylation as measured by 5mC levels were significantly lower in DIPG compared to pediatric GBM (p < 0.001), adult GBM (p < 0.01), and normal brain (p < 0.01). Conversely, 5hmC levels were significantly higher in DIPG compared to pediatric GBM (p < 0.0001) and adult GBM (p < 0.0001). Additionally, in an independent set of DIPG tumor samples, TET1 and TET3 mRNAs were found to be overexpressed relative to matched normal brain. CONCLUSIONS: Our findings extend the immunohistochemical study of epigenetic alterations in archival tissue to DIPG specimens. Low H3K27me3, decreased 5mC and increased 5hmC are characteristic of DIPG in comparison with extrapontine GBM. In DIPG, the relative imbalance of 5mC compared to 5hmC may represent an opportunity for therapeutic intervention. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/2051-5960-2-59) contains supplementary material, which is available to authorized users.